Saving Wall Street or main street - Markus Haavio; Antti Ripatti; Tuomas Takalo (Bank of Finland, 2016)
​We build a dynamic stochastic general equilibrium model, where the balance sheets of both banks and non-financial firms play a role in macro-financial linkages. We show that in equilibrium bank capital tends to be scarce, compared with firm capital. We study public funding of banks and firms in times of crisis. Government capital injections can be useful as a shock cushion, but they distort incentives. Small capital injections benefit banks more than firms but the relative benefit is declining in the injection size. Government should first recapitalize banks, and if resources are large enough, lend to firms too.
URN:NBN:fi:bof-201605131125
Keywords: E44; G21; G28; G38; 330